Export Decision under Risk - José De Sousa; Anne-Célia Disdier; Carl Gaigné (Center for Economic Studies and ifo Institute (CESifo), 2016)
Using firm and industry data, we establish two facts: (i) Uncertainty about demand conditions not only reduces export sales and exporting probabilities but also makes exports less sensitive to trade policy; (ii) the most productive exporters are more affected by higher industry-wide expenditure volatility than the least productive exporters. We rationalize these regularities by developing a new firmbased trade model wherein managers are risk averse. Higher volatility induces the reallocation of export shares from the most to the least productive incumbents. Greater skewness of the demand distribution and/or higher trade cost weaken this effect. Our results hold for a large class of consumer utility functions.
Keywords: D21; D22; F12; F14; 330; firm exports; demand uncertainty; risk aversion; expenditure volatility; skewness